Bibliometric analysis of the graduation projects in Geography of the University of Costa Rica, 1966-2021 - Masís Campos, Ramón (2022)
The authors carried out a bibliometric study and a detailed analysis of the various variables of the final graduation projects developed in the Geography Career of the University of Costa Rica (UCR). This research responds to the need to quantify and analyze the different aspects of the scientific production of the student body, which had not been done exhaustively until now. The purpose of the publication is to disclose the results found, to make visible and demonstrate the efficiency and usefulness of these investigations. Similarly, it urges their leaders to strengthen those weak aspects and promote current issues and address the needs of the context. The basic methodological steps focused on document reviewed and consulted from the database of the System of Libraries and Documentation of the University of Costa Rica (SIBDI). Data were extracted from this base and processed with the tools of the Libreoffice and QGIS software. One of the most relevant results is that the School of Geography-UCR has supported the development of 141 final graduation projects from 1966 to 2021, for an annual average of 2.6, which have not only consisted on an academic requirement, but many of them have been input for the attention of national and international problems.